Okoljska odgovornost, izzivi in priložnosti trajnostnega delovanja skozi perspektivo študentov Univerze v Mariboru - Kozmus, Andreja; Pšunder, Mateja (Komuniciranje okoljske krize, 2025)
This paper presents the results of a survey on environmental issues conducted among an ad hoc sample of 435 students at the University of Maribor (UM). We found that students are aware of and concerned about environmental problems. Students who perceive environmental issues more problematic and are more concerned about them, are, according to their own assessment, more pro-environmental. The biggest obstacle to pro-environmental behaviour is funding, and they attribute responsibility for dealing with the environmental crisis to various stakeholders. Students who perceive fewer barriers to pro-environmental behaviour and attribute more responsibility for managing the environmental crisis to individuals express higher self-rated pro-environmental behaviour and a greater desire to be informed. Their knowledge of the range of environmental issues at UM is low and they want UM to take actions that do not affect them too personally. The survey showed some differences between students according to gender and level of education and some links between them, and gave some ideas for practice.